Anxiety Level During the Second Localized COVID-19 Pandemic Among Quarantined Infertile Women: A Cross-Sectional Survey in China - Cao, Lian-Bao; Hao, Qianjie; Liu, Yan; Sun, Qiang; Wu, Bing; Chen, Lili; Yan, Lei (Frontiers in Psychiatry, 2021)
Infertility usually causes mental health problems for patients and bad emotions such as anxiety and depression can also adversely affect women's normal pregnancy. We aimed to compare the anxiety level of female infertility patients in quarantined and non- quarantined areas during the second wave of COVID-19 epidemics. A total of 759 participants were included in this cross-sectional study. Anxiety was measured by the State-Trait Anxiety Inventory (STAI). Participants were divided into the quarantined group (QG) and non-quarantined group (Non-QG). There was no significant difference in the average STAI score of the two groups of infertile women, but responses to the emotional state showed that women in the QG had a higher tendency to anxiety. Participants in QC spent more time paying attention to the dynamics of the epidemic every day, and their sleep (p<0.01) and mood conditions were worse (p<0.01) than in the Non-QG. Through the research on the infertility treatment information of the overall research population, it is found the average STAI-S (p=0.031) score and STAI-T (p=0.005) score of women who were infertile for more than three years were significantly higher than those of women with less than two years; the STAI-T score of infertile women who underwent in vitro fertilization (IVF) was higher than that of non-IVF women (p=0.007), but not was the STAI-S score. To conclude, although the second wave of quarantine during COVID-19 epdimic did not significantly increase anxiety in infertile women, it did lead to an increase in other negative emotions and worse family relationships. Patients with long-term infertility treatment and those who need to do IVF are more anxious subgroups.